Development of Socio-Scientific Issue-Based E-Modules on Addictive Substances to Enhance Students’ Chemical Literacy - Lestari, Mia; Helsy, Imelda; Irwansyah, Ferli Septi; Sari, Sari; Dahriah, Iis; Hakim, Grace Martian (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Chemical literacy is an essential competency that includes understanding chemical concepts, critical thinking skills, and scientific-based decision-making in dealing with relevant social issues. Based on this urgency, this study aims to develop an e-module based on Socioscientific Issues (SSI) on addictive substances as an effort to develop chemical literacy. This study uses the R&D method with the ADDIE (Analyze, Design, Development, Implement, and Evaluation) model up to the Development stage to develop an e-module based on sociosatific issues. The research sample includes two material experts, one media expert, and 15 Chemistry Education students of UIN Sunan Gunung Djati Bandung as respondents for the acceptability test. Data were collected using validation sheets and questionnaires, then analyzed descriptively to determine the validity and feasibility of the e-module. The validation results of two material experts and one media expert showed an average score of the material aspect of 0.90, language 0.89, and appearance 0.87 (very valid). The student feasibility test showed a score of the material aspect of 92.22%, language 89.33%, and appearance 88.22% (very feasible). This e-module is feasible to be used as an innovative and contextual learning media and the basis for further development of the implementation and evaluation stages. This study presents a novelty in the form of an interactive e-module based on socio-scientific issues (SSI) for addictive substances material in Android format (.apk). This e-module is relevant for digital learning and is designed to improve students' chemical literacy by linking chemical concepts to real problems and training critical thinking and science-based decision making.